Extreme Risk Analysis on Financial Derivatives in Indonesia Using Extreme Value-at-Risk Based on Generalized Pareto Distribution (GPD) - Febrianty, Popy (International Journal of Global Operations Research, 2025)
Develop a Value at Risk (VaR) model based on Generalized Pareto Distribution (GPD) to analyze extreme risks in financial derivative portfolios in Indonesia. The GPD approach is chosen because it can describe the tail distribution of price data that exceeds a certain threshold. Price data (in US dollars/USD) of financial derivatives from the Indonesian market are collected from 2011 to 2022 taken from the International Financial Statistics (IMF Data). Furthermore, the data is analyzed to determine the threshold, then the GPD model is applied to extract the tail distribution. The calculation of GPD-based VaR is carried out to provide a more accurate estimate of the potential for extreme losses. This study is expected to contribute to the management of extreme risks in the derivatives market in Indonesia, as well as provide guidance for investors and financial institutions in making more informed investment decisions.